Visual Culture Transformation in the Myths of Prince Samudra - Asep Yudha Wirajaya (International Journal of Science and Applied Science: Conference Series, 2022)
The Prince of Samudra Myths is a story about a noble preacher who experienced a "historical twist" so that now people are more familiar with the figure of the preacher as the figure behind the myth of pesugihan on Mount Kemukus. The Regional Government of Sragen Regency also has difficulty in restoring the image of the preacher. Therefore, various strategic steps were sought to normalize the deviated flow of historical stories. Among them is physical development which is expected to change the mindset of the community. In addition, a short film was also made as part of an effort to correct history. This article will focus on the visual culture transformation contained in the process of regenerating the Prince Samudra myths which were made into short films in the docudrama genre. With this study, it is hoped that the meaning that occurs in the visual culture transformation process of the Prince Samudra docudrama film can be revealed